Clinical Spectrum and Neuroimaging Characteristics of Arterial Ischemic Stroke in Childhood: Experience in a Tertiary Care Hospital - Akter, Naznin; Anwar, Sayeda; Samshad, Iffat Ara; Akter, Shaheen (Journal of Enam Medical College, 2024)
Background: Arterial ischemic stroke in children is rare but may be associated with mortality and significant neurological morbidity. Clinical manifestations and underlying etiology of pediatric ischemic stroke differ from adult stroke. This study aimed to detect the common presentations with their neuroimaging characteristics along with probable etiology of pediatric stroke in a tertiary care hospital of Bangladesh. Materials and Methods: This cross-sectional observational study was conducted in Dhaka Medical College Hospital (DMCH) during period of June 2017 to December 2020 among 65 children aged 29 days to 14 years diagnosed with acute arterial ischemic stroke. Children with acute onset of focal neurological sign with evidence of acute parenchymal ischemic infarction on brain MRI were included as study population. Children diagnosed with hemorrhagic stroke, history of perinatal stroke and cerebral venous sinus thrombosis (CVST) were excluded from the study. Results: Majority of studied children came from rural areas with male predominance. Hemiparesis was the most common presenting feature, then speech disturbance, headache, seizure, visual disturbance and behavioral abnormalities. Thirty-four percent had history of recurrence. Arteriopathy was present among 37% of studied population and moyamoya disease was the common variety. Single infarction with unilateral distribution was seen on radiology imaging among 74% of studied population. Moyamoya disease as etiology and presence of multiple infarcts with bilateral distribution on neuroimage were significantly associated with stroke recurrence. Conclusion: Early diagnosis of pediatric stroke and early search of underlying etiology is essential to prevent mortality, long term neurological morbidity and further recurrence. J Enam Med Col 2022; 12(1): 36−42